An 18,200-dalton adrenal protein that contains four [Met]enkephalin sequences. - Kilpatrick, D L (1982)
An 18,200-dalton adrenal enkephalin-containing polypeptide was purified to homogeneity and shown to contain four internal [Met]enkephalin sequences. Protein sequence analysis and mapping of trypsin-derived peptides demonstrated that the previously described 12,600-dalton and 5,300-dalton adrenal enkephalin-containing polypeptides compose the amino-terminal and carboxyl-terminal sequences, respectively, of this larger protein. They are linked by two basic amino acid residues to form the entire sequence of the 18,200-dalton protein. This protein is the largest enkephalin-containing polypeptide yet isolated from beef adrenal medulla and serves as the precursor for several other previously characterized adrenal enkephalin-containing proteins and peptides.